Estudio de un modelo de robot con auto balanceo (2021)
In this undergraduate project a self-balancing robot system is studied. The study has two parts: a simulation of the dynamical behavior of the robot with several controllers and a prototype implementation. For the simulation, a number of controllers were developed and tested using a non-linear and a linearized model of the robot. The controllers are based on the state feedback theory, and they consider incrementally realistic situations, such as access to states, reconstruction of state, partial state feedback among others. Their performance is analyzed using various input signals and comparing their transient efficiency and the required control effort. Lastly, the design of a real prototype based on the model is presented, and a controller selected from the simulations was implemented and tested to examine its ability in keeping the prototype in equilibrium.